Peran Kepala Desa Dalam Reformasi Birokrasi Pelayanan Publik Di Desa Sambibulu, Kecamatan Taman, Kabupaten Sidoarjo - Hamdan Aisy Zuhdan; Rachmawati Novaria; Adi Soesiantoro (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The role of the village head in bureaucratic reform refers to an action or contribution provided by a leader to improve a bureaucratic system to be better than before. The background of this research is due to the lack of bureaucracy responsiveness in public services in Sambibulu Village, Taman District, Sidoarjo Regency. Therefore, the research objective is to identify and analyze the role of the village head in bureaucratic reform of public services in Sambibulu Village, Taman District, Sidoarjo Regency. This research is qualitative in nature with data collection techniques including interviews, observations, and documentation. The informants are the Village Head, Village Secretary, and the villagers of Sambibulu. The theory used refers to the Servant Leadership theory by Barbuto & Wheeler (2006) which includes indicators such as Altruistic Calling, Emotional Healing, Wisdom, Persuasive Mapping, and Organizational Stewardship. The results of this study show that overall, the role of the village head in bureaucratic reform of public services in Desa Sambibulu is very significant. Through commitment, wisdom, and effective leadership, he acts as a change agent driving the establishment of a more efficient, responsive, and quality public service system. In addition, the village head is actively involved in various aspects ranging from democratic values, openness to community participation, to the ability to lead with an innovative approach. The Village Head of Sambibulu plays a role in realizing quality public services oriented towards community interests. However, there is still a gap between public expectations and reality, such as inconsistency in implementing responsive public services.